Pengaruh Motivasi Kerja dan Kepuasan Kerja Terhadap Organizational Citizenship Behavior pada Karyawan PT BPR Nusantara Bona Pasogit 17 - Br S. Meliala, Diva Regita; Harahap, Kartini; Siregar, Onan Marakali (Jurnal Serambi Ekonomi dan Bisnis, 2024)
In today's increasingly competitive digital business era, the foundation of product innovation so that companies can continue to grow lies in human resources. In realizing its goals, the company needs qualified employees, who demonstrate citizenship behavior that is able and willing to do more than just ordinary tasks, beyond the demands of the company to provide performance that exceeds expectations known as organizational citizenship behavior. This study aims to determine the effect of work motivation and job satisfaction partially and simultaneously on organizational citizenship behavior in employees of PT BPR Nusantara Bona Pasogit 17.  This research uses quantitative methods with an associative approach. Sampling was carried out through sampling techniques with saturated sampling methods, and used 31 respondents as samples.  Primary data used was obtained through direct questionnaire distribution and secondary data obtained through literature studies.  The data analysis technique uses instrument test, validity test, reliability test, classical assumption test, multiple linear regression analysis and hypothesis testing. The results showed that work motivation has no partial effect on organizational citizenship behavior, obtained a tcount value of 1.9442.04841 with a significance level of 0.0620.025. Job satisfaction has a partial effect on organizational citizenship behavior, obtained a tcount value of 3.9682.04841 with a significance level of 0.0000.025. Work motivation and job satisfaction simultaneously affect organizational citizenship behavior, obtained fcount value 9.5453.34 with a significance level of 0.0010.05 and the coefficient of determination of 36.3% while the remaining 63.7% is influenced by other variables not included in the research variables.